Analysis of Government Policy on Islamic Education Subjects in Public Schools - Suroso; Moh. Nasrudin (Saniya Institute, 2024)
This research is based on the fact that the subject of Islamic religious education (PAI) in public schools has undergone a long and complex development along with the socio-political conditions that occur. Government policies on Islamic religious education applied in public schools are the purpose of this research. In this research, the literature review method was used to find out the chronology of the emergence of each government policy. The results show that the state continues to support PAI in schools. The Indonesian government has set a policy that Muslim students can study Islam in all public schools. The purpose of this policy is to improve the quality of education by teaching Islam in schools. The government is responding to the needs of Muslim students to develop their spiritual potential. As a result, the education system in Indonesia continues to undergo social, political and cultural changes over time.